THE HORMONAL CROSSTALKS INSIDE SANTORIO ON HIS WEIGHING CHAIR - Nina Mohorko (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Santorio Santorio studied metabolism by spending decades on a weighing chair, studying influences of changes in body weight on human health and well-being. Today, metabolism research is oriented to hormonal crosstalks that regulate plasma glucose levels, amount of fat deposits in adipose tissue and feeding. In search for brain acting metabolism controlling factors, endocrine function has been observed in organs previously not thought as endocrines, such as stomach and white adipose tissue. Stomach is the main ghrelin secreting organ, while white adipose tissue the main leptin secreting organ. These two opposing hormones act on hypothalamus to regulate energy homeostasis - ghrelin in the case of negative energy balance and leptin in the case of increased amount of fat deposits in adipose tissue. The two hormones display a circadian pattern in their secretion. In fact, the regulation of metabolism is controlled by the circadian clock, but also the circadian clock itself is strongly influenced by food intake, with stomach oxyntic cells being a possible food-entrainable oscillators.